Óleo de palma em dietas para pós-larvas de tilápia do Nilo - Alves, Luiz Fernando de Souza (2017)
The inclusion of lipid sources in diets for Nile tilapia (Oreochromis niloticus) becomes a viable alternative as an energy source for low cost. The objective of this study was to include the palm oil in the diet of post-larvae of Nile tilapia, evaluating the performance, atrato and palatability of the diets, check the profile and quantify the methyl esters of fatty acids of the oil palm. We used 400 post-larvae of Nile tilapia with seven days after hatching (average weight starting at 28 ± 5 mg), distributed in 20 tanks of fiber glass cylindrical-conical with a volume of 20 liters. The experiment was conducted in a completely randomized design with five treatments and four replications. The treatments were included in a partial and total palm oil, with the inclusion of 0.0; 1.5; 3.0; 4.5 and 6%. Were observed concentrations of monounsaturated fatty acids and saturated fats in palm oil, noting a high quantity of palmitic and stearic, oleic and linoleic acid. In the performance of post-larvae were observed significant differences (P<0.05) for the variables final weight, length, weight gain, specific growth rate and condition factor. There were no significant differences (P>0.05) for atrato and palatability of the diets. Based on the information obtained in the present study, it is concluded that the inclusion of at least 3% of palm oil in the phase of masculinization for post-larvae of tilapia contributes to the improvement of the productive parameters.